ANALISIS EVALUASI KURIKULUM PAI DI SDN BAKTI DENGAN PENDEKATAN MODEL CIPP (CONTEXT, INPUT, PROCESS DAN PRODUCT) - Angga Permana; Ade Andriyani; Mohamad Erihadiana; Asep Nursobah (Universitas Islam Lamongan, 2025)
This research aims to analyze the Islamic Education curriculum using the CIPP evaluation model. The method used is field research. The research results show that in the context of learning, students' low socioeconomic background affects their learning facilities. Nevertheless, the Islamic Education curriculum aligns with the school's vision of shaping students with noble character. In terms of input, Islamic Education teachers have met the standards set by the government, but they still face challenges due to lack of teaching materials and limited technological learning media. In the learning process, teachers consistently use diverse methods tailored to learning objectives and utilize technology, albeit with limitations. Regarding the product aspect, student learning outcomes are quite good, with nearly 75% reaching the minimum completion criteria. However, some students still cannot read the Quran, and there is a need for cooperation among various educational stakeholders.